The Ipsilateral Adjacent Laminae: A Reliable Guide in Determining the Direction of Subaxial Cervical Pedicle Axis in the Sagittal Plane. Issue 21 (November 2015) - Yan, Jun; Li, Ka; Zheng, Yanping; Li, Bo; Sun, Zhiyuan; Li, Jianmin
Abstract : Study Design: A retrospective radiographic analysis and applied anatomical study. Objective: The aim of this study was to evaluate the relationships between the ipsilateral lamina/laminae and pedicle axis in the sagittal plane, and the feasibility of free hand pedicle screw placement in subaxial cervical spine without intraoperative fluoroscopic guidance. Summary of Background Data: The morphology of subaxial cervical spine pedicle has been studied extensively. However, to our knowledge, no study has specifically evaluated the relationships between the ipsilateral lamina/laminae and pedicle axis in the sagittal plane on computed tomography (CT) reconstruction images. Methods: Axial CT images of 70 adult cases were obtained. Multi-directional pedicle axis reconstruction images of subaxial cervical spines were analyzed. Both the angle formed by the direction of ipsilateral lamina to the pedicle axis in the oblique sagittal plane (lamina-pedicle angle, LPA) and the angle formed by the tangential line passing the ipsilateral adjacent outer laminae cortex to the pedicle axis in the oblique sagittal plane (tangential line pedicle angle, TPA) were recorded. On the basis of the radiographic data, a "T"-shaped guiding tool was designed, and the accuracy of free hand subaxial pedicle screw placement using the guiding tool was evaluated in 12 cadavers. Results: A total of 350 vertebrae were analyzed. Averaged LPA ranged from 72.2 degrees at C3 to 84.2 degrees at C6, averaged TPA ranged from 89.8 degrees at C3 to 90.7 degrees at C6. The TPA showed a high level of consistency close to a right angle. A total of 115 inserted subaxial cervical pedicle screws on 12 cadavers were evaluated. The rate of screw insertion without pedicle wall penetration was 98%, and the rate of pedicle wall penetration of more than 2 mm in the sagittal plane was 0%. Conclusions: The TPA serves to be a reliable guide in determining the direction of subaxial cervical pedicle axis in the sagittal plane. Free hand placement of subaxial pedicle screw is feasible under the guidance of the newly designed guiding tool based on TPA. Level of Evidence: 5